2020
DOI: 10.1002/pi.6087
|View full text |Cite
|
Sign up to set email alerts
|

Deduction of a facile method to construct Antheraea mylitta silk fibroin/gelatin blend films for prospective biomedical applications

Abstract: Blend films of two types (I and II) were prepared by mixing Antheraea mylitta silk fibroin (AMF) and gelatin solution in various blend ratios via the solution casting method. Two different crosslinkers, namely glutaraldehyde and genipin, were used during blend preparation. The structural characteristics and thermal properties of the blend films were examined by Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), Thermogravimetric analysis (TGA) and Diffrential scanning calorimetery (DSC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…In one of our previous study on silk fibroin gelatin blend films, the enzymatic degradation was found to be varying with change in the distribution of crystallinity in the molecular structures, the blends with higher crystallinity showed slower biodegradation. [59] She et al have reported similar correlation of high crystallinity and low biodegradation for B. mori silk fibroin films. [60] In this study, the samples incorporating CTAB-MT clay showed less degradation as compared to their corresponding blends without clay, this could be attributed to the altered hydrophilicity and reduced porosity of the material as a result of clay introduction.…”
Section: Biodegradationmentioning
confidence: 79%
See 2 more Smart Citations
“…In one of our previous study on silk fibroin gelatin blend films, the enzymatic degradation was found to be varying with change in the distribution of crystallinity in the molecular structures, the blends with higher crystallinity showed slower biodegradation. [59] She et al have reported similar correlation of high crystallinity and low biodegradation for B. mori silk fibroin films. [60] In this study, the samples incorporating CTAB-MT clay showed less degradation as compared to their corresponding blends without clay, this could be attributed to the altered hydrophilicity and reduced porosity of the material as a result of clay introduction.…”
Section: Biodegradationmentioning
confidence: 79%
“…Preparation of Modified Clay Doped Nanowebs: Silk fibroin stock solution (10% w/v) was prepared following the method described in a previously reported work. [59] PVA stock solution (10% w/v) was prepared using formic acid as solvent. These two solutions were mixed together in blend ratios 50:50 and 30:70 to prepare PSNF50 and PSNF70 blend solutions, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S100 film showed 42.68% β-sheet crystallinity which is in close agreement with our previous studies and the data reported in literature for wild type regenerated silk fibroin. 25,33 P30S70, P50S50 and P70S30 showed 24.88%, 11%, and 10.36% crystallinity, respectively.…”
Section: Morphological and Structural Analysismentioning
confidence: 97%
“…The surface roughness might have appeared as a consequence of incubating the blend films in methanol to regenerate the crystallinity similar to observations made in our previous studies on non-mulberry silk fibroin materials. 7,25 Rough surface morphology is generally pragmatic to support cell attachment in biomaterials. 26 In most of the studies reported in literature, clear phase separation has been observed in silk fibroin and PVA blends, only one study reported by Um et al presented homogeneous morphology through SEM but the variety of silk used was mulberry.…”
Section: Morphological and Structural Analysismentioning
confidence: 99%